Dietary Restriction and Nutrient Balance in Aging. (23rd November 2015) - Santos, Júlia; Leitão-Correia, Fernanda; Sousa, Maria João; Leão, Cecília
Abstract : Dietary regimens that favour reduced calorie intake delay aging and age-associated diseases. New evidences revealed that nutritional balance of dietary components without food restriction increases lifespan. Particular nutrients as several nitrogen sources, proteins, amino acid, and ammonium are implicated in life and healthspan regulation in different model organisms from yeast to mammals. Aging and dietary restriction interact through partially overlapping mechanisms in the activation of the conserved nutrient-signalling pathways, mainly the insulin/insulin-like growth factor (IIS) and the Target Of Rapamycin (TOR). The specific nutrients of dietary regimens, their balance, and how they interact with different genes and pathways are currently being uncovered. Taking into account that dietary regimes can largely influence overall human health and changes in risk factors such as cholesterol level and blood pressure, these new findings are of great importance to fully comprehend the interplay between diet and humans health.